Antioxidant Treatment Improves Cardiac Dysfunction in a Murine Model of Premature Aging. Issue 5 (November 2016) - Hemmeryckx, Bianca; Hohensinner, Philipp; Swinnen, Melissa; Heggermont, Ward; Wojta, Johann; Lijnen, Henri Roger
Abstract : Abstract: Bmal1-(brain and muscle ARNT-like protein-1) deficient (Bmal1 −/− ) mice prematurely age because of an increased reactive oxygen species (ROS) production. These mice also show a decline in cardiac function with age. We investigated whether an antioxidant treatment can ameliorate the declining cardiac function in prematurely aged Bmal1 −/− mice. Male Bmal1 −/− and wild-type (Bmal1 +/+ ) mice were exposed for 15 weeks to a high fat and high cholesterol diet with or without the antioxidant 4-hydroxy-2, 2, 6, 6-tetramethylpiperidin-1-oxyl (TEMPOL; 5 mmol/L; in drinking water during the last 10 weeks). Echocardiographic analysis revealed that TEMPOL treatment of Bmal1 −/− mice normalized cardiac function, as evidenced by a decrease in left ventricular diastolic and systolic internal diameters, and by an increase in fractional shortening and ejection fraction. The antioxidant did not affect cardiac function in Bmal1 +/+ mice. Although TEMPOL did not influence cardiac ROS levels in Bmal1 −/− mice, it significantly protected Bmal1 −/− cardiac telomeres from oxidation, as evidenced by a reduction in the telomere damage score (0.11 ± 0.012% vs. 0.16 ± 0.015%; P = 0.028). Thus, antioxidant treatment normalized cardiac function of Bmal1 −/− mice, probably in part by scavenging ROS.